2004
DOI: 10.1212/01.wnl.0000129983.06983.4e
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-positive paraneoplastic neurologic syndromes

Abstract: FDG-PET imaging is useful in tumor screening of patients with antineuronal antibodies, but should be complemented by CT scanning to increase sensitivity and accuracy of tumor diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 28 publications
1
74
0
6
Order By: Relevance
“…In adult patients, the tumor search should be directed at the most common underlying tumors, that is, high-resolution CT of the chest and abdomen, and gynecological examination and mammography (or MRI of the breasts) [56]. When this is negative, FDG-PET should be considered [22,61].…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…In adult patients, the tumor search should be directed at the most common underlying tumors, that is, high-resolution CT of the chest and abdomen, and gynecological examination and mammography (or MRI of the breasts) [56]. When this is negative, FDG-PET should be considered [22,61].…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…Recent studies investigated the performance of whole-body 18 F-FDG PET/CT in relation to paraneoplastic antibody status (16). Several studies showed that whole-body 18 F-FDG PET and 18 F-FDG PET/CT are highly useful in the screening of patients with suspected paraneoplastic syndrome and positive paraneoplastic antibodies (9,10). However, a recent study by Vatankulu et al suggested that paraneoplastic antibody presence should not be an indispensable factor for performing 18 F-FDG PET/CT in patients suspected of harboring a paraneoplastic syndrome (16).…”
Section: Discussionmentioning
confidence: 99%
“…The details of the study design, patient demographics and characteristics, paraneoplastic presentation, paraneoplastic antibody status, index test, proportion of patients diagnosed with underlying malignancy, and reference standards of each included study were summarized in Supplemental Tables 2 and 3 (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(28)(29)(30)(31). Among the 24 studies included in the qualitative assessment, 4 studies were prospective and 20 studies were retrospective.…”
Section: Study Characteristics and Methodologic Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations